Plane wave, pattern subtraction, range compensation. - Leatherwood, D.A.
Plane wave, pattern subtraction (PWPS) range compensation improves the performance of far field and compact, antenna pattern measurement systems by compensating errors introduced by antenna measurement facility (range) imperfections. The range-field model consists of a plane wave that represents an ideal range field plus a selectable number of plane waves representing range field imperfections. The error patterns introduced by the undesired range-field plane waves are estimated and subtracted from the measured pattern to produce a compensated pattern. This compensated pattern is used to obtain an improved estimate of the error patterns. This iterative procedure is continued until the compensation algorithm converges. The antenna measurement range field is measured on the surface of a sphere enclosing the test zone, and a plane-wave model of this range field is constructed
Keywords: Antenna measurement facility; Antenna under test; Compact antenna pattern measurement systems; Error compensation; Error patterns; Far field pattern measurement systems; Field pattern measurement systems; Iterative procedure; Plane wave pattern subtraction range compensation; Plane-wave model; Range-field model